INCREASING STUDENTS' INTEREST IN LEARNING THROUGH SINGING METHOD IN CLASS 3 UPTD SDN 017125 BINJAI SERBANGAN - Agustriana, Hafsah; Nana Mardiana; Ulil Azmi (PT. Antis International Publisher, 2025)
Objective: This study aims to increase the learning interest of grade 3 elementary school students through the application of the singing method on Pancasila material in Civic Education (PPKn) subjects. The singing method was chosen because it can create a pleasant learning atmosphere, make it easier for students to remember the material, and increase learning motivation. Method: This learning improvement uses PTK steps for 2 cycles. Cycle 1 was carried out on Wednesday, April 30, 2025 with the steps of the singing method. Cycle I learning is good but still needs improvement, so learning improvement is needed for cycle II. Cycle II was held on Wednesday, May 7, 2025. The research subjects were 3rd grade students of SDN 017125 Binjai Serbangan Asahan Regency totaling 20 students. Results: The results showed that the application of the singing method can increase students' interest and motivation to learn. This is evidenced in the pre-cycle as many as 6 people became (30%), increased in cycle I to 12 students (70%) and in cycle II experienced an increase again to 20 students (100%). Thus, the singing method is effectively used to increase students' interest in learning Pancasila material in Civics subjects in grade 3 SDN 017125 Binjai Serbangan Asahan Regency. Novelty: This PKP report is entitled Efforts to Increase Student Learning Interest Through the Singing Method on Pancasila Material for Civic Education Subjects in Class 3 UPTD SDN 017125 Binjai Serbangan. This research was made in the framework of the Professional Capacity Building (PKP) course assignment. This PKP report is a requirement for obtaining a Bachelor of Education degree from the Open University.